2003
DOI: 10.1136/sti.79.1.42
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of disclosure of genital herpes to partners

Abstract: Objective: To identify factors which determine whether and when patients will disclose infection with genital herpes to sexual partners. Methods: The sample was 26 women and 24 men attending a herpes clinic in a sexually transmitted disease clinic. Semistructured interviews yielded quantitative data and also qualitative data which were subjected to content analysis. Results: Characteristics of partners were very important in determining whether disclosure occurred. Respondents were less likely to tell partners… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
46
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 6 publications
8
46
1
Order By: Relevance
“…Individuals in longer relationships were also statistically more likely to disclose than those in shorter relationships. This is consistent with findings by Green et al (2003), who suggested that disclosure is more likely to occur in serious, longer term, and committed relationships.…”
Section: Discussionsupporting
confidence: 93%
“…Individuals in longer relationships were also statistically more likely to disclose than those in shorter relationships. This is consistent with findings by Green et al (2003), who suggested that disclosure is more likely to occur in serious, longer term, and committed relationships.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with research focusing on other HIV'/ populations (e.g. Greene et al , 2003) and on disclosure of other sexually transmitted diseases such as genital herpes (Green et al , 2003). Whether the availability of treatment for HIV disease, and hence the increased practical value of informing them, was a factor in the very high rates of disclosure to partners in this sample relative to samples reported from Africa may be worth further investigation.…”
Section: Discussionsupporting
confidence: 88%
“…Greene et al , 2003) and regarding disclosure of genital herpes (Green et al , 2003), predicted outcomes were important in determining whether disclosure would occur. The one example in this study where an individual did not disclose to a long-term partner was the result of predictions of an adverse reaction.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with research in genital herpes populations 10. It might also be predicted that those who expect a worse partner response to disclosure might be less likely to disclose.…”
supporting
confidence: 88%